2016
DOI: 10.1021/acs.est.5b05749
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in Drinking Water in Shanghai and Their Contribution to Antibiotic Exposure of School Children

Abstract: A variety of antibiotics have been found in aquatic environments, but antibiotics in drinking water and their contribution to antibiotic exposure in human are not well-explored. For this, representative drinking water samples and 530 urine samples from schoolchildren were selected in Shanghai, and 21 common antibiotics (five macrolides, two β-lactams, three tetracyclines, four fluoquinolones, four sulfonamides, and three phenicols) were measured in water samples and urines by isotope dilution two-dimensional u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(69 citation statements)
references
References 39 publications
0
66
0
3
Order By: Relevance
“…In another drinking water source in Shanghai, 11 ARGs were detected with high concentrations, and sul II was present at the highest concentration (4.19 × 10 8 copies/L). This phenomenon might reflect the widespread use of sulfonamides in this region [19]. Furthermore, ARGs could be transferred between bacteria through transposons, plasmids and integrons [44].…”
Section: Discussionmentioning
confidence: 98%
“…In another drinking water source in Shanghai, 11 ARGs were detected with high concentrations, and sul II was present at the highest concentration (4.19 × 10 8 copies/L). This phenomenon might reflect the widespread use of sulfonamides in this region [19]. Furthermore, ARGs could be transferred between bacteria through transposons, plasmids and integrons [44].…”
Section: Discussionmentioning
confidence: 98%
“…Several epidemiological studies have reported that antibiotic use in children was positively associated with obesity in children[1922]. Recently, several studies have reported extensive exposure of school-aged children to antibiotics by measuring antibiotics in urine, and certain antibiotics, such as florfenicol and trimethoprim, were related to obesity [23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…The security of tap water is always concerned in the world, especially in developing country. Currently, the antibiotics are not considered as one kind of organic contaminant in tap water, but some of them have been detected because the present conventional wastewater treatment plants cannot completely remove the antibiotics . In this study, the recovery of LVSS was investigated in real sample.…”
Section: Resultsmentioning
confidence: 99%